Review of key management techniques for advanced metering infrastructure - Otisitswe Kebotogetse; Ravi Samikannu; Abid Yahya (International Journal of Distributed Sensor Networks)
The electricity industry has been developed through the introduction of the smart grid. This has brought about two-way communication to the grid and its components. The smart grid has managed to increase the efficiency and reliability of the traditional power grid over the years. A smart grid has a system that is used to measure and collect readings for power consumption reflection, and the system is known as the Advanced Metering Infrastructure. The advanced metering infrastructure has its components too which are the smart metre, metre control system, collector or concentrator and communication networks (wide area network, neighbourhood area network, and home area network). The communication networks in the advanced metering infrastructure have created a vulnerability to cyber-attacks over the years. The reliability of the power grid to consumers relies on the readings from the smart metre, and this brings about the need to secure the smart metre data. This article presents a review of key management methods in advanced metering infrastructure environments. The article begins with an overview of advanced metering infrastructure and then shows the relationship between the advanced metering infrastructure and the smart grid. The review then provides the security issues related to advanced metering infrastructure. Finally, the article provides existing works of key management methods in advanced metering infrastructure and future directions in securing advanced metering infrastructure and the smart grid.